Farvebilleder fra det mørke Afrika - Race, krop, økonomi og politik i Mahamet-Saleh Harouns Grigris - Baggesgaard, Mads Anders (K&K - Kultur og Klasse, 2015)
Analyzing Tchadian director Mahamet-Saleh Haroun’s 2013 film Grigris the article discusses the political potentials of contemporary Sub-Saharan Film. The article rejects frameworks of African and Francophone cinema and argues that a localized understanding of this film in Chad provides a better understanding of the universal and global reach of the engagement with politics that is one of the film’s prime objectives. It is through an understanding of the local and regional society and history that it becomes evident how the film engages with political issues with reach far beyond the borders of Chad. This engagement is performed through the screening of bodies, of race highlighting the role that these entities play in Chadian society and Chadian politics.